2016
DOI: 10.1016/j.socscimed.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative patient-provider communication and uptake of adolescent vaccines

Abstract: Rationale Recommendations from healthcare providers are one of the most consistent correlates of adolescent vaccination, but few studies have investigated other elements of patient-provider communication and their relevance to uptake. Objective We examined competing hypotheses about the relationship of patient-versus provider-driven communication styles with vaccination. Methods We gathered information about vaccine uptake from healthcare provider-verified data in the 2010 National Immunization Survey-Teen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 37 publications
1
59
1
Order By: Relevance
“…16,17 Similarly, Moss and colleagues found that among a probability sample of 4121 parents of adolescents from the National Immunization SurveyTeen, HPV vaccination coverage was higher among adolescent girls of parents who recalled "efficient" provider communication about HPV vaccination than those who recalled participatory discussions. 18 We speculate that announcements normalize HPV vaccination for both providers and parents, making providers more likely to raise the topic and parents more likely to consent to vaccination. In contrast, our conversation training did not increase HPV vaccine initiation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…16,17 Similarly, Moss and colleagues found that among a probability sample of 4121 parents of adolescents from the National Immunization SurveyTeen, HPV vaccination coverage was higher among adolescent girls of parents who recalled "efficient" provider communication about HPV vaccination than those who recalled participatory discussions. 18 We speculate that announcements normalize HPV vaccination for both providers and parents, making providers more likely to raise the topic and parents more likely to consent to vaccination. In contrast, our conversation training did not increase HPV vaccine initiation.…”
Section: Discussionmentioning
confidence: 97%
“…Announcements are commonly used for early childhood vaccines and other routine clinical care. Furthermore, analyses of videotaped clinician encounters 16,17 and a nationally representative survey 18 suggest that announcements are associated with higher vaccine uptake. Alternatively, a "conversation" approach that engages parents in open-ended discussions may build rapport and thus increase parental openness to HPV vaccination for their children.…”
mentioning
confidence: 99%
“…Some research studies have suggested that a presumptive approach, treating vaccination as routine and something that will happen as a matter of course during the healthcare visit, is best at encouraging vaccination. 17,18 Other correlational studies report evidence of the benefits of a shared approach for vaccination, 10,19 though a recent randomized trial found that a shared approach did not improve vaccination attitudes. 20 Similarly, in this study, we found that collaborative (or shared) communication style was associated with the highest rates of HPV vaccination, with particularly strong positive associations for rural and non-Hispanic white girls.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that collaborative communication was associated with HPV vaccine uptake. 92 However, traditionally underserved groups, such as parents of Hispanic and nonprivately insured adolescents, were less likely to report collaborative communication, which adversely affected HPV vaccination coverage for these groups. 93 Qualitative research generally supported the finding that providers were less likely to engage non-English speaking parents or parents from disadvantaged backgrounds in HPV vaccine-related communication.…”
Section: Contentmentioning
confidence: 99%